2004
DOI: 10.1002/jsfa.1873
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid: pharmaceutical functions, preparation and applications in foods

Abstract: Ferulic acid (4-hydroxy-3-methoxycinnamic acid), an effective component of Chinese medicine herbs such as Angelica sinensis, Cimicifuga heracleifolia and Lignsticum chuangxiong, is a ubiquitous phenolic acid in the plant kingdom. It is mainly conjugated with mono-and oligosaccharides, polyamines, lipids and polysaccharides and seldom occurs in a free state in plants. Ferulic acid is a phenolic acid of low toxicity; it can be absorbed and easily metabolized in the human body. Ferulic acid has been reported to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
457
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 767 publications
(471 citation statements)
references
References 80 publications
5
457
0
9
Order By: Relevance
“…The different capital letters after the values in the same column indicate that one-way ANOVA of the means is different significantly (P<0.05) revealed that the quality of the set-yoghurt prepared from the HRP-treated milk was improved. Treatment of food proteins with H 2 O 2 and peroxidase cause oxidative cross-linking of tyrosine residues and FA can increase the degree of crosslinking (Ou and Kwok 2004). The present results are consistent with this finding, and the set-yoghurt prepared from HRP and FA-treated milk showed the best quality indices.…”
Section: Resultssupporting
confidence: 90%
“…The different capital letters after the values in the same column indicate that one-way ANOVA of the means is different significantly (P<0.05) revealed that the quality of the set-yoghurt prepared from the HRP-treated milk was improved. Treatment of food proteins with H 2 O 2 and peroxidase cause oxidative cross-linking of tyrosine residues and FA can increase the degree of crosslinking (Ou and Kwok 2004). The present results are consistent with this finding, and the set-yoghurt prepared from HRP and FA-treated milk showed the best quality indices.…”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, from a biorefinery perspective, these compounds are potentially of interest as there is a market for these products. For instance, ferulic acid is widely used in the food and cosmetic industries: It is used as the raw material for the production of vanillin and preservatives, as a cross-linking agent for the preparation of food gels and edible films and as an ingredient in sports foods and skin protection agents [47]. Ferulic acid can also be biocatalytically converted into other useful aromatic chemicals including vanillin, styrene and vinylguaiacol [48].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, complete cell disruption and significant change in surface morphology were observed (Fig. 8b) for cells treated with 40 lM native FA which may be attributed to its free radical scavenging ability (Ou and Kwok 2004). Studies have revealed that phenolic compounds such as FA at higher concentrations may act as pro-oxidant interacting with transition metal ions found in biological systems which lead to oxidative damage of normal cellular components (Maurya and Devasagayam 2010;Galati and O'Brien 2004).…”
Section: Cytocompatibility Evaluationmentioning
confidence: 94%